Comparative Analysis of Real Costs and INA CBG's Rates in BPJS Kesehatan Patients with Schizophrenia - Oktarina Mahanggi; Abdul Rahem; Yunita Nita (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Schizophrenia is the most severe mental disorder because its risk of death is to 2-3 times higher. Objective: To determine the average real costs, the difference between real costs and INA-CBG rates of inpatients with schizophrenia, and the factors that affect real costs. Methods: The study was conducted retrospectively from the hospital perspective using the total sampling method from January 2020-December to 2021. The study sample included inpatients patients and the real costs of the hospital. The data obtained were analyzed using the Mann-Whitney U-test and multiple linear regression tests. Results: About 112 patients met the inclusion criteria. The average real cost of inpatients with schizophrenia at Tombulilato General Hospital from January 2020 to December 2021 is Rp. 9,895,102 and the average INA-CBG rate of inpatients with schizophrenia was Rp. 14,820,778. There was a difference between the real costs and INA-CBG rates (p = 0.002), with the highest average hospital real cost component in the inpatient room (Rp. 3,397,723 (34.34%). The factor that affected the real costs of inpatients with schizophrenia patients is the length of stay (p = 0.000). Conclusion: The real costs of the hospital were lower (p = 0.002) than those of the INA-CBG. The highest real cost of the hospital was the inpatient room (34.34%), and the factor that affected the real costs was the length of stay (p = 0.000).